Implementasi Teknologi Augmented Reality Pada Game Beat Saber di Game Blink Padang - Kurniasih, Kurniasih; Sari, Putri Yunita; Prihamdani, Ferju; Maideshinta, Tri Kurnia; Rinaldi, Muhammad; Fiddaraini, Hasana; Putri, Harmida Gusnia; Novita, Rini (Journal of Computer Science and Information System(JCoInS), 2024)
This research aims to explore and implement Augmented Reality (AR) technology in the Beat Saber game at Game Blink Padang. Augmented Reality is a technology that combines the real world with virtual objects to create an immersive interactive experience for users. Beat Saber is a musical rhythm game that is popular among game lovers, where players have to cut incoming blocks according to the rhythm of the music being played. It is hoped that the implementation of AR in this game can improve the playing experience by adding more interesting and realistic visual and interaction elements. This research involves evaluating the user experience of the AR version. Research methods include data collection through surveys and direct observation by playing the Blink Padang Game. The research results show that the use of AR in Beat Saber significantly increases player satisfaction and engagement. Players report a more fun and challenging gaming experience, as well as improvements in immersion and interactivity. The implementation of AR technology opens up new opportunities in the development of music rhythm games and can become a model for the integration of AR in other games in the future.